Environmental assessment of solid state recycling routes for aluminium alloys: Can solid state processes significantly reduce the environmental impact of aluminium recycling?. Issue 1 (2015) - Duflou, Joost R.; Tekkaya, A. Erman; Haase, Matthias; Welo, Torgeir; Vanmeensel, Kim; Kellens, Karel; Dewulf, Wim; Paraskevas, Dimos
Abstract: Solid state recycling techniques allow the manufacture of high density aluminium alloy parts directly from production scrap. In this paper the environmental impacts associated with 'meltless' scrap processing routes based on three different techniques, namely hot extrusion, screw extrusion and spark plasma sintering (SPS), are compared with the corresponding remelting route as reference. Analysis of the obtained results allows clear conclusions on the perspectives offered by solid state recycling for systematic environmental impact reduction of aluminium recycling with material and energy savings as most important influencing factors. An overall impact reduction with a factor 2 for the SPS route and 3–4 for the extrusion routes is found to be realistic.